Effect of Na2O content, SiO2/Na2O molar ratio, and curing conditions on the compressive strength of FA-based geopolymer. (1st August 2017) - Cho, Young-Keun; Yoo, Sung-Won; Jung, Sang-Hwa; Lee, Kwang-Myong; Kwon, Seung-Jun
Highlights: Quantitative investigation of curing temperature for FA-based geopolymer strength. Various micro-observation results through EDA, XRD, SEM, MIP. Strength grading contour considering alkali-activators, Ms values, and curing temperatures. Relationship between strength and changes in macro-pore structure. Pre-curing effect with different temperature and duration on strength. Abstract: Many researches have been performed on performance improvement of geopolymer considering low calcium materials and alkaline solutions. In the binder of geopolymer, OPC (Ordinary Portland Cement) which can cause environmental load such as CO2 emission is not used. The mechanical properties of geopolymer are directly affected by various parameters like binder types, SiO2 /Na2 O molar ratios, alkali activator concentrations, and curing conditions (temperature and period), but very limited researches have been performed on comprehensive evaluation of the influencing parameters. In the work, compressive strength in FA (Fly Ash)-based geopolymer is evaluated considering four test variables covering Na2 O content, SiO2 /Na2 O molar ratios, curing temperature/period, and pre-curing temperature/period. The results reveal that higher compressive strength can be obtained with higher Na2 O content, higher curing temperatures, and longer pre-curing periods at the relatively low temperature (23 °C). On the other hand, an extension of curing period at high temperatures leads to strength reduction due to increasing macro-pores over 50 nm. Through the various tests, strength grade contours considering SiO2 /Na2 O molar ratios, Na2 O content, and curing temperatures are obtained, which can be utilized for an effective mix design for FA-based geopolymer.